Ecogeografia e diversidades genética e química de Lippia aff. rotundifolia Cham. - Meira, Messulan Rodrigues (2016)
It was aimed with this thesis to characterize the ecogeography, genetic and chemical diversity of Lippia rotundifolia Cham. (Verbenaceae) in natural populations of the State of Minas Gerais, Brazil. To achieve the goal, ecogeographic features in 13 sites of five mesoregions in Minas Gerais were made. The studied sites were Gigante and Rio do Peixe in the city of Botumirim, Rio Tigre in the city of Gouveia, Joaquim Felício in the same city, São Gonçalo do Rio das Pedras in the city of Serro, Abóboras Community in the city of Montes Claros, Serra Nova State Park in Rio Pardo de Minas city, APA de Olhos D'água in the same city, State Park of Veredas do Peruaçu in the city of Cônego Marinho, Quedas do Rio Bonito Ecological Park in the city of Lavras, Private Reserve of the Natural Heritage Brumas do Espinhaço in the city of Lapinha, Santana do Riacho in the same city and State Park of Rio Preto in São Gonçalo do Rio Preto. The environments were located through hikes in Cadeia do Espinhaço and through consultation of the Virtual Herbarium of Flora and Fungi database information. The sites were georeferenced for production of the thematic cards and the data analysis. Among the ecogeographic characteristics, the degree of anthropism, burnings, climatic aspects (altitude, rainfall, temperature) and physical-chemical soil properties were addressed. For the study of diversity, samples for botanical identification and vegetative propagation were collected. Possessing the cultivated material in a greenhouse the genetic and chemical composition were analyzed. For the genetic diversity it was used markers of ISSR type and for chemical analysis, the static headspace technique and gas chromatography connected to the mass spectrometer. From the results, the Lippia rotundifolia proved to be generalist with regarding to ecogeographic and edaphoclimatic factors and occurs in sandy and hyper dystrophic soils with low genetic variability and large number of chemical compounds. The higher molecular variability of the species occurs between individuals of each environment being that the population of Rio Tigre in the city of Gouveia is the most genetically distant. Sixty-seven compounds were detected in eleven environments. The access of São Gonçalo do Rio das Pedras, in Serro, holds the largest chemical abundance in relative area. The volatiles compounds myrcene, β-linalool and caryophyllene are the most common detected by the species. It is hoped that this research encourages other studies with native species of medicinal potential aiming the rational use of genetic and chemical resources of the native flora.